2021
DOI: 10.1186/s12885-021-07846-0
|View full text |Cite
|
Sign up to set email alerts
|

A prognosis-related molecular subtype for early-stage non-small lung cell carcinoma by multi-omics integration analysis

Abstract: Background Early-stage non-small cell lung carcinoma (NSCLC) accounts for more than 80% of lung cancer, which is a kind of cancer with high heterogeneity, so the genetic heterogeneity and molecular subtype should be explored. Methods Partitioning Around Medoid algorithm was used to acquire the molecular subtype for early-stage NSCLC based on prognosis-related mRNAs and methylation sites. Random forest (RF) and support vector machine (SVM) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Even though prior research studies [35] were able to identify molecular subtypes for NSCLC in its early stages, immune gene-based molecular typing is still relatively uncommon. In this study, immune-related genes were utilized to classify early-stage NSCLC samples from the RNAseq and GSE datasets into two subgroups (C1 and C2).…”
Section: Discussionmentioning
confidence: 99%
“…Even though prior research studies [35] were able to identify molecular subtypes for NSCLC in its early stages, immune gene-based molecular typing is still relatively uncommon. In this study, immune-related genes were utilized to classify early-stage NSCLC samples from the RNAseq and GSE datasets into two subgroups (C1 and C2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported different LUAD subtypes based on methylation or gene expression (12,13). Moreover, methylation and gene expression have been combined to identify the pathologic subtypes of NSCLC, including small cell lung cancer and LUAD, instead of molecular typing (14).…”
Section: Introductionmentioning
confidence: 99%
“…Human crystallin alpha B ( CRYAB ), also known as human alpha B-crystallin (HspB5) or αB-crystallin, is a subtype of small heat shock protein (sHsp). It was first discovered in the lens of the eye and has been linked to a variety of diseases, including eye disease, heart disease and even breast, lung, prostate and ovarian cancers ( 1 ). CRYAB comprises of an N-terminal domain, a central domain, and a C-terminal domain ( 2 ).…”
Section: Introductionmentioning
confidence: 99%